Numerical study on the behavior of link-to-column connections in eccentrically braced frames - Fakhredin Danesh; Mohammad ali Faridalam (Numerical Methods in Civil Engineering)
Geometry of eccentrically braced frames (EBFs) in some cases causes the connection of link beam to the column. The details of such conditions should be studied carefully due to the full plastic rotation in the link beam. In this research, the behavior of link-to-column connection is modeled and the failure modes are considered. Based on the previous researches shear link can exhibit better behavior in such conditions. However, different models are designed and analyzed using finite element method to investigate the influence of short, medium and long link beams on the failure modes of the connections. Two types of connections are applied in designing these models. The results show that models with access hole in connection details are failed before achieving 50% full plastic rotation in the link beams. Besides, in the connections without access hole, the link beams behave as ductile elements and experience up to 90% full plastic rotation that are recommended by the codes.